Optimizing Tissue Culture for Yellow Dragon Fruit (Selenicereus megalanthus) Propagation: Enhancing Shoot and Root Induction - Dirga, Kate Tiffany; Maryuandini, Ufi; Sachio, Sachio; Sukma, Dewi (Department of Agronomy and Horticulture, IPB University, 2025)
Yellow dragon fruit (Selenicereus megalanthus)